Social Robotics: 8th International Conference, ICSR 2016, Kansas City, MO, USA, November 1-3, 2016 Proceedings - Agah, Arvin; Cabibihan, John-John; Howard, Ayanna; Salichs, Miguel A; He, Hongsheng (Lecture Notes in Computer Science, 2016)
This book constitutes the refereed proceedings of the 8th International Conference on Social Robotics, ICSR 2016, held in Kansas City, MO, USA, in November 2016. The 98 revised full papers presented were carefully reviewed and selected from 107 submissions.The theme of the 2016 conference is Sociorobotics: Design and implementation of social behaviors of robots interacting with each other and humans. In addition to technical sessions, ICSR 2016 included three workshops: The Synthetic Method in Social Robotics (SMSR 2016), Social Robots: A Tool to Advance Interventions for Autism, and Using Social Robots to Improve the Quality of Life in the Elderly.